PENGARUH KOMPENSASI DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION PADA HOTEL RESTY MENARA PEKANBARU - Rahman, Hadi; Andri, Seno (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine how much influence the compensation and organizational commitment on turnover intention. The sample in this study was taken as many as 52 respondents and the technique used was census technique. The data in this study used the survey method through questionnaires filled out by employees. Data obtained using simple regression analysis and multiple regression analysis. The results of this study indicate that Compensation has a negative and significant effect on turnover intention. Organizational commitment has a negative and significant effect on turnover intention. And simultaneously compensation and organizational commitment have a negative and significant effect on turnover intention.Keywords: Compensation, Organizational Commitment, and Turnover intention